HUBUNGAN UKURAN LINGKAR LEHER DENGAN INDEKS MASSA TUBUH PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA ANGKATAN 2016 - IRFAN DARFIKA LUBIS; ASIYAH HARAHAP (JURNAL ILMIAH KOHESI, 2021)
Neck circumference as an index of subcutaneous fat distribution is used to identify individuals who are overweight throughmeasurement of body mass index. A high body mass index accounts for 4 million deaths globally. Early and rapidassessment of obese individuals can increase disease risk stratification. This research method is a descriptive analytic studywith a cross-sectional approach. Research subjects were 118 UMSU Faculty of Medicine students, class of 2016 consistingof men and women who met the inclusion and exclusion criteria. The sampling technique uses total sampling. Neckcircumference with BMI in male samples obtained p value = 0,000 and r value = 0.853. Neck circumference with BMI infemale samples obtained p value = 0,000 and r value = -0,789. neck circumference with BMI as a whole obtained values of p= 0,000 and r = 0.332. There was a significant correlation between neck circumference with BMI in a sample of male andfemale UMSU Faculty of Medicine students in 2016, with the level of closeness being moderate (p = 0,000; r = 0.332). Thegreater the circumference of the neck, the greater the BMI.